Main barriers to ICT teacher training and disability - Marta Montenegro Rueda; José Fernández Cerero (Research in Social Sciences and Technology, 2019)
From the earliest ages, the commitment to an inclusive education needs the impulse of an educational system that opens its schools to all students. This reality would not be possible today without taking into account the educational support provided by Information and Communication Technologies (ICT) to the inclusive process, since they constitute the scaffolding that will allow participation and the realization of tasks adjusted to the possibilities and interests of the people. In the process of integration of ICT in the classroom, teachers are a key element since, as has been shown in numerous studies, one of the critical factors for the success of educational systems is the existence of trained, motivated teachers. The purpose is to know the main barriers or obstacles for the development of teacher training plans in ICT for people with disabilities, as well as the priority aspects for training. In the empirical part of the study, 241 interviews with professionals from the Spanish educational sector (members of management teams, ICT coordinators, directors and technological advisors of teacher training centers) were analyzed. Among the conclusions, we can highlight that the main barriers that hinder the implementation of ICT training activities and disability in most of the autonomous communities are determined in the first place by economic factors, lack of time, and teachers’ attitude. The conclusions of the study make it necessary to adopt important measures in the initial training of teachers in order to be trained in the incorporation and appropriate use of ICT in teaching people with different types of disabilities, especially taking into account that the reality that we face every time has more innovative and enriching technological tools that offer us a wide range of applications and adequate tools for this purpose.